Kewenangan Pemerintah Daerah dalam Pelaksanaan Pengawasan terhadap Perhimpunan Pemilik dan Penghuni Satuan Rumah Susun - Setiaprameswari, Dwiluna (Journal Evidence Of Law, 2023)
This study aims to describe the authority of the Regional Government in supervising and controlling the feasibility of building functions and to analyze or describe the imposition of sanctions on building owners who violate the feasibility of building functions based on the results of supervision and control by the government. The type of method in this research is normative legal research, namely research conducted by examining laws and regulations, legal concepts, and legal theory to be applied to a particular problem. The results of this study are to determine the limits of the authority of the Regional Government in supervising the formation of associations of apartment owners and occupants and the imposition of sanctions on the formation of associations of apartment owners and occupants based on the results of supervision flat occupants. In the management of flats, it is necessary to regulate the interests of the owners and occupants through an association of flat owners formed by the flat owners in order to realize the right of every person to meet the needs of a decent life and a safe place to live. life. In this regard, the government's role in terms of supervision is very important as a control in ensuring the formation of associations of apartment owners and tenants.